Tele-EEG: Current Applications, Challenges, and Technical Solutions - Rosenow, Felix; Audebert, Heinrich J.; Hamer, Hajo; Hinrichs, Hermann; Kessler-Uberti, Stephanie; Kluge, Tilmann; Noachtar, Soheyl; Remi, Jan; Sotoodeh, Ali; Strzelczyk, Adam; Weber, Joachim E.; Zoellner, Johann Philipp (Klinische Neurophysiologie, 2018)
Telemedicine for people with epilepsy aims to facilitate a thorough diagnosis and therapy regardless of regional constraints. In Germany, this is especially important in rural regions. This review aims to outline current tele-epileptological applications, with a special regard to the individual frameworks, demands, challenges and technical solutions. The requirements of pediatric tele-epileptology are explored. Special considerations are given to the technical and diagnosis guidelines required to review tele-EEG. Projects conducted in the recent past demonstrate positive results in patient care.
EVALuna2:201946